Boron-doped graphene nanosheet-supported Pt: a highly active and selective catalyst for low temperature H2-SCR. Issue 21 (22nd May 2018) - Hu, Maocong; Yao, Zhenhua; Li, Lili; Tsou, Yung-Hao; Kuang, Liyuan; Xu, Xiaoyang; Zhang, Wen; Wang, Xianqin
Abstract : Pt/BG catalysts synthesized with a one-step hydrothermal method showed enhanced H2 -SCR activity and selectivity to N2 at 105 °C via a bifunctional catalytic mechanism. Abstract : A series of boron-doped graphene-supported Pt (Pt/BG) nanosheets were designed and synthesized using a one-step facile hydrothermal method. ICP, XPS, and TPD results confirmed that boron atoms were successfully embedded into the graphene matrix. The selective catalytic reduction of nitric oxide with hydrogen (H2 -SCR) was tested over Pt/BG catalysts. The multi-roles of doped-boron were investigated by Raman, BET, CO-chemisorption, H2 -TPD, XPS, and NO-TPD. Boron doping led to a higher dispersion and smaller size of Pt nanoparticles, facilitated hydrogen spillover, promoted more metallic Pt formation, and increased both H2 and NO chemisorption, which were attributed to an enhanced Pt nucleation rate over doped-boron, electron donation from boron to Pt, and extra chemisorption sites. The reaction performances (conversion 94.7%, selectivity 90.3%, and TOF 0.092 s −1 ) were greatly promoted attributing to a bifunctional catalytic mechanism. This work paves the way to modify the structure and tune the chemisorption ability of graphene-based catalysts, and provides novel insights for designing high performance catalysts.